3D printed microfluidic Coulter counter for blood cell analysis. Issue 14 (28th June 2022) - Yan, Jiasheng; Wang, Chuang; Fu, Yusheng; Guo, Jiuchuan; Guo, Jinhong
Abstract : Schematic of the Coulter principle of the analysis box. Abstract : Coulter counters are ubiquitous in everyday life; however, with reduced orifice size shrinkage, there is an increased risk of clogging. Herein, a 3D microfluidic printing-based single-use kit is presented for analyzing biological samples and performing accurate Coulter cell count analysis ( e.g., white blood cells in the blood). The gem hole eliminates the traditional design concept of integration inside the detection instrument, innovatively causing it to be independent from the analysis instrument. Further, integrating the hole in the analysis box enables the design of a separate detection module. The analysis box is disposable, convenient, and hygienic; avoids cross-infection; solves the problem of clogging of tiny holes from a new perspective; and no longer requires uneconomical and inconvenient methods, such as flushing, cauterization, and fluid focusing, through solid water flow. Further development of the newly designed 3D printing analysis box can enable its extensive use in POCT (point-of-care) detection scenarios. Moreover, through mass production, the issue of cost will be eliminated.